MELANOMA MALIGNO DA MUCOSA NASAL - DOIS CASOS CLINICOS - Neves, Marta; Pires, Joana; Trigueiros, Nuno; Duarte, Delfim; Magalhães, Fátima; Lopes, Gustavo; Leonardo, Abílio; Galán, Teresa; Maia Gomes, A. (Revista Portuguesa de Otorrinolaringologia-Cirurgia de Cabeça e Pescoço, 2005)
.